Revealing the Gender Bias in the Interpretation of Al-Manar (Critique of the Epistemology of the Interpretation of QS. An-Nisā’: 34) - Faridatun Nisa; Naila Magfira Alwasi; Nurfiati (al-Afkar, Journal For Islamic Studies, 2025)
Muhammad Abduh’s life was closely intertwined with modernization, yet his interpretations reveal gender biases that have not been addressed in previous research. Abduh’s views on the relationship between men and women in the household align with the structural-functional theory, which posits that role differentiation is linked to gender. Based on this problem, this paper examines the epistemological foundation employed by Muhammad Abduh in interpreting QS. An-Nisā’: 34, a verse often used to justify male superiority over women. This study employs a qualitative method with critical analysis using conflict theory, which, in the author’s view, is related to Marxist-Socialist feminist theory. The findings indicate that Muhammad Abduh utilized the burhani method and the adabi ijtima’i approach. Furthermore, to strengthen his arguments, Abduh employed linguistic analysis, munasabah ayat, the use of riwayat, and comparative analysis. From this interpretative flow, these two lines of thought lead to role inequality because everything is measured based on physical attributes or fitrah. QS. An-Nisā’: 34 should be understood based on two periods, namely the time of the Prophet and the modern era, so that a common thread can be drawn regarding the differences in social conditions between the two. Thus, an understanding based on gender in determining role differentiation cannot be maintained because role dominance is determined by the social conditions of society.